DROP OUT PENGOBATAN HIV PADA IBU BERDASARKAN FAKTOR PREDISPOSISI DI KABUPATEN BANYUMAS TAHUN 2016 - Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
HIV-infected women must face challenges and threats such as doctor's verdicts about HIV-positiveness, people's stigma, HIV testing, the handling problems, poverty, and gender roles. Long-term treatment is frequent in every chronic illness, including HIV-AIDS, treatment including antiretroviral (ARV) medication, prophylaxis, or treatment for opportunistic infections. The adherence of therapy is the most essential thing to suppress HIV replication and avoid the occurrence of resistance. This study is aimed to acquire the detailed and in-depth description of the case of Drop-Out HIV Treatment to mothers in Banyumas District in 2016. The method of Qualitative research with case study design. The Informants selection of in this study was conducted by using non-probability sampling technique, how to collect the data in-depth interview method (indepth interview). the main Informants are mothers who are dropped out in HIV treatment as much as 5 people. The secondary informants are husband/family and health workers. The results showed that the duration drop out of HIV treatment between 7 - 16 months, when lost follow-up had opportunistic infection forming tuberculosis and ulcers on neck The side effects of ARV treatment experienced were nausea, dizziness and itching of skin, The mothers' limited understanding inÂ  how to take medication and its benefits, beliefs about HIV treatment and treatment benefits.